Penggunaan Asap Cair terhadap Masa Simpan Ikan Cakalang (Katsuwonus pelamis) - Deyvie Xyzquolyna; Muh. Sudirman Akilie (Fakultas Pertanian Universitas Ichsan Gorontalo, 2016)
This study aimed to determine the effect of period immersion in liquid smoke to water content, protein content and total microbes, and the shelf life of skipjack. This research method was using a completely randomized design with two factors: the first the period of immersion for 10, 20 and 30 minutes and storaged for 0, 2, 4 and 6 weeks. The results showed that, the skipjack without stored had water content as much as 71.5%, 71.69%, and 73.96% for 10, 20 and 30 minutes perriod immersion. The following stored at the second and sixth week, the water content of skipjack reduced. At the fourth week, the water content for period immersion 10 and 30 minutes were increased. Period immersion in liquid smoke led to an increased of protein content of skipjack. The result showed that the higher protein content obtained in skipjack with period immersion for 30 minutes and without stored was 10.44%. The total microbes decreased by the increasing period of immersion skipjack in liquid smoke. However, during the storage total microbes were increased.